Molecular epidemiology of coxsackievirus A6 derived from hand, foot, and mouth disease in Fukuoka between 2013 and 2017. Issue 11 (24th July 2018) - Yoshitomi, Hideaki; Ashizuka, Yuki; Ichihara, Sachiko; Nakamura, Tomofumi; Nakamura, Asako; Kobayashi, Takayuki; Kajiwara, Junboku
Abstract : Coxsackievirus (CV)‐A6 has been the primary causative agent of hand, foot, and mouth disease (HFMD) in Japan since 2011. In Fukuoka, CV‐A6‐associated HFMD caused epidemics in 2013, 2015, and 2017. This paper reports the genetic characteristics of the CV‐A6 entire viral protein 1 (VP1) derived from patients with HFMD in Fukuoka between 2013 and 2017. CV‐A6 was detected in 105 of 280 clinical specimens, and the entire VP1 sequences could be analyzed for 90 of the 105 specimens. Phylogenetic analysis revealed that the CV‐A6 strains were classified into clade A and subgrouped into subclade A3 or subclade A4. Each subclade strain carried amino acid substitutions in the presumed DE and GH loops of the VP1, and no amino acid substitutions were identified as deleterious to the protein function. No significant difference was found in the clinical symptoms between the genetic subclades using statistical analyses. In conclusion, this study clarified the genetic diversity of CV‐A6 in Fukuoka from 2013 to 2017. The emergence of the CV‐A6 strains was classified into derived new subclades based on phylogenetic analysis of the VP1 gene that may cause CV‐A6‐associated HFMD epidemics approximately every 2 years.